Dual isotope evidence for sedimentary integration of plant wax biomarkers across an Andes-Amazon elevation transect. (1st December 2018) - Feakins, Sarah J.; Wu, Mong Sin; Ponton, Camilo; Galy, Valier; West, A. Joshua
Highlights: Leaf wax biomarkers were studied in soils and rivers from the Andes to the Amazon. Elevation trend found in C and H isotopic compositions of plant wax in soils. Plant wax in river-suspended sediments approximated uniform spatial integration. Carbon isotopic composition of n -alkanes differentiated with depth in soil and river. Petrogenic inputs of n -alkanes discerned by CPI and dual isotopic analyses. Abstract: Tropical montane regions tend to have high rates of precipitation, biological production, erosion, and sediment export, which together move material off the landscape and toward sedimentary deposits downstream. Plant wax biomarkers can be used to investigate sourcing of organic matter and are often used as proxies to reconstruct past climate and environment in sedimentary deposits. To understand how plant waxes are sourced within a wet, tropical montane catchment, we measure the stable C and H isotope composition ( δ 13 C and δ D) of n -alkanes and n -alkanoic acids in soils along an elevation transect and from sediments within the Madre de Dios River network along the eastern flank of the Peruvian Andes, draining an area of 75, 400 km 2 and 6 km of elevation. Soils yield systematic trends in plant wax δ 13 C (+1.75 and +1.31‰ km −1, for the C29 n -alkanes and C30 n -alkanoic acids respectively in the mineral horizon) and δ D values (−10 and −12‰ km −1, respectively) across a 3.5 km elevation transect, which approximates trends previously reported from canopy leaves, though we find offsets between δ 13 C values in plants and soils. River suspended sediments generally follow soil isotopic gradients defined by catchment elevations ( δ 13 C: +1.03 and +0.99‰ km −1 and δ D: −10 to −7‰ km −1, for the C29 n -alkanes and C30 n -alkanoic acids respectively) in the wet season, with a lowering in the dry season that is less well-constrained. In a few river suspended sediments, petrogenic contributions and depth-sorting influence the n -alkane δ 13 C signal. Our dual isotope, dual compound class and seasonal sampling approach reveals no Andean-dominance in plant wax export, and instead that the sourcing of plant waxes in this very wet, forested catchment approximates that expected for spatial integration of the upstream catchment, thus with a lowland dominance on areal basis, guiding paleoenvironmental reconstructions in tropical montane regions. The dual isotope approach provides a cross-check on the altitudinal signals and can resolve ambiguity such as might be associated with vegetation change or aridity in paleoclimate records. Further, the altitude effect encoded within plant waxes presents a novel dual-isotope biomarker approach to paleoaltimetry.